Disturbed soil properties and geotechnical design - Schofield, A. N. 1930-; Haigh, Stuart (ICE Publishing, 2018)
This is an easily accessible account of critical state of soil mechanics, geotechnical centrifuge testing and the original Cam-Clay model invented by the author.